2019
DOI: 10.1039/c8nj05520c
|View full text |Cite
|
Sign up to set email alerts
|

Azulenes with aryl substituents bearing pentafluorosulfanyl groups: synthesis, spectroscopic and halochromic properties

Abstract: Azulenes with SF5-containing substituents gave significantly different spectroscopic responses to protonation depending on the regioisomer in question.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 89 publications
0
11
0
Order By: Relevance
“…Under these conditions, the 4,4,5,5‐tetramethyl‐1,3,2‐dioxaborolanyl group was introduced into the 2‐positions of azulenes with good selectivity. [ 7,8,26,29,30 ] Considering both the total yields of borylated products 2 and 3 as well as the number of equivalents of the Bpin unit in pin 2 B 2 , both boryl groups in bis(pinacolato)diboron (pin 2 B 2 ) are employed in the reaction. [ 26,30 ]…”
Section: Functionalization Of Azulene Through Metal‐catalyzed Cross‐c...mentioning
confidence: 99%
See 2 more Smart Citations
“…Under these conditions, the 4,4,5,5‐tetramethyl‐1,3,2‐dioxaborolanyl group was introduced into the 2‐positions of azulenes with good selectivity. [ 7,8,26,29,30 ] Considering both the total yields of borylated products 2 and 3 as well as the number of equivalents of the Bpin unit in pin 2 B 2 , both boryl groups in bis(pinacolato)diboron (pin 2 B 2 ) are employed in the reaction. [ 26,30 ]…”
Section: Functionalization Of Azulene Through Metal‐catalyzed Cross‐c...mentioning
confidence: 99%
“…[ 7,8,26,29,30 ] Considering both the total yields of borylated products 2 and 3 as well as the number of equivalents of the Bpin unit in pin 2 B 2 , both boryl groups in bis(pinacolato)diboron (pin 2 B 2 ) are employed in the reaction. [ 26,30 ]…”
Section: Functionalization Of Azulene Through Metal‐catalyzed Cross‐c...mentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst the azulene core has been incorporated into a wide variety of colorimetric chemical probes (exploiting the vivid colours it is famous for) [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ], this review will focus on those published probes that exploit the fluorescent nature of azulene. The nature of azulene fluorescence is highly dependent on substitution around the azulene core, which affects whether emission is more dominant from the S 2 or S 1 singlet excited state (a notable exception from this can be found in the work of Zhu et al, who showed that emission of azulene aldehydes can occur from the S 3 or S 2 excited state dependent on the nature of the hydrogen bonding present [ 31 , 32 ]).…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Upon exposure to acidic solutions, azulene takes up a proton at its 1-position to form the azulenium cation which is stabilized via a 6-π-electron aromatization of the seven-membered ring. [6] These properties have driven studies of the potential applications of azulene in advanced electronics, such as optoelectronic devices, [7][8][9][10][11][12] nonlinear optics, [13] charge transport, [14] and sensory applications, [15][16][17][18][19][20][21][22][23][24] which have been comprehensively reviewed elsewhere. [25][26][27] Azulene has also been incorporated into interesting molecules such as squaraine, [28] boron-dipyrromethene, [29] and porphyrin.…”
Section: Introductionmentioning
confidence: 99%